Bahan Ajar Interaktif Berbasis Etnomatematika Bali untuk Meningkatkan Kemampuan HOTS Siswa Kelas III SD - Kadek Ariyani; I Wayan Widiana; I Made Suarjana (Universitas Pendidikan Ganesha, 2024)
This research was motivated by the need for more learning resources and the low HOTS abilities of students in elementary schools. Therefore, this research aims to develop interactive teaching materials based on Balinese ethnomathematics to improve students' HOTS abilities. This research is a type of research and development method that uses qualitative and quantitative data. The research model used is the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The data collection methods used are test and non-test methods, with data collection instruments in the form of multiple-choice tests and questionnaires. The subjects in this research were validation experts and third-grade students at SD Negeri 3 Penarukan. The research results showed that interactive teaching materials obtained a validity index 0.957 with very high content validity qualifications. Second, the practical value of the product obtained an assessment result of 97% with very good qualifications. Third, the significance value (2-tailed) in the correlated t-test shows that interactive teaching materials based on flat figures based on Balinese ethnomathematics effectively improve the HOTS abilities of third-grade elementary school students. Thus, this development research can positively contribute to learning that is more contextual and relevant to local culture, especially in Bali. This interactive teaching material can be a reference for teachers to improve the quality of learning in schools and maintain cultural heritage and local wisdom.